2015
DOI: 10.1111/nph.13568
|View full text |Cite
|
Sign up to set email alerts
|

Arctic plant origins and early formation of circumarctic distributions: a case study of the mountain sorrel, Oxyria digyna

Abstract: SummaryMany plant species comprising the present-day Arctic flora are thought to have originated in the high mountains of North America and Eurasia, migrated northwards as global temperatures fell during the late Tertiary period, and thereafter attained a circumarctic distribution. However, supporting evidence for this hypothesis that provides a temporal framework for the origin, spread and initial attainment of a circumarctic distribution by an arctic plant is currently lacking.Here we examined the origin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 63 publications
3
45
0
Order By: Relevance
“…Recent phylogeographic studies of arctic‐alpine plant species have revealed that their genetic variation is typically highly structured due to several major geographic barriers that facilitated range separation (17 species, Eidesen et al., ; Silene acaulis , Gussarova et al., ). A few studies have estimated that major lineages within arctic‐alpine plants diverged prior to the middle Pleistocene ( Saxifraga oppositifolia , Abbott, ; Abbott & Comes, ; Vaccinium uliginosum , Alsos, Engelskjøn, Gielly, Taberlet, & Brochmann, ; Oxyria dygina , Wang et al., ), consistent with Hultén's () hypothesis of an early Pleistocene origin of their circumarctic ranges. However, several phylogeographic studies also suggest that some arctic‐alpine plants are capable of extensive long‐distance dispersal ( V. uliginosum , Alsos et al., ; Cassiope tetragona , Eidesen, Carlsen, Molau, & Brochmann, ; Saxifraga rivularis , Westergaard, Jørgensen, Gabrielsen, Alsos, & Brochmann, ), even from Alaska to southern South America ( Empetrum , Popp, Mirre, & Brochmann, ).…”
Section: Introductionmentioning
confidence: 56%
“…Recent phylogeographic studies of arctic‐alpine plant species have revealed that their genetic variation is typically highly structured due to several major geographic barriers that facilitated range separation (17 species, Eidesen et al., ; Silene acaulis , Gussarova et al., ). A few studies have estimated that major lineages within arctic‐alpine plants diverged prior to the middle Pleistocene ( Saxifraga oppositifolia , Abbott, ; Abbott & Comes, ; Vaccinium uliginosum , Alsos, Engelskjøn, Gielly, Taberlet, & Brochmann, ; Oxyria dygina , Wang et al., ), consistent with Hultén's () hypothesis of an early Pleistocene origin of their circumarctic ranges. However, several phylogeographic studies also suggest that some arctic‐alpine plants are capable of extensive long‐distance dispersal ( V. uliginosum , Alsos et al., ; Cassiope tetragona , Eidesen, Carlsen, Molau, & Brochmann, ; Saxifraga rivularis , Westergaard, Jørgensen, Gabrielsen, Alsos, & Brochmann, ), even from Alaska to southern South America ( Empetrum , Popp, Mirre, & Brochmann, ).…”
Section: Introductionmentioning
confidence: 56%
“…3–4 Ma at a time when global temperature decreased sharply (Matthews & Ovenden, ; Zachos, Pagani, Sloan, Thomas, & Billups, ). However, this study only focused on the QTP and further studies involving a finer sampling across the entirely distribution of P. nutans associated with large‐scale genomic data should be employed to gain a detailed knowledge of evolutionary history of this species (e.g., Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These loci were previously surveyed in a study of populations of O. digyna (Table , Supporting information; Wang et al . ). DNA extractions and PCR amplifications, using homologous primers, were conducted following the procedures described by Wang et al .…”
Section: Methodsmentioning
confidence: 97%
“…We excluded from this analysis other O. digyna populations outside Asia because during and following colonization of these other regions, they might have been subject to mutation fixation rates and climatic oscillations different to those of Asian populations (Wang et al . ). The four demographic scenarios examined were (i) continuous population expansion since the origin of the two species, (ii) recent expansion, (iii) expansion–shrinkage and (iv) expansion–shrinkage–expansion.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation